Primary Peritonitis without Abdominal Signs Causing a Diagnostic Dilemma: A Case Report - Chaitra Govardhan; Veerabhadra Radhakrishna; Christi Dominic Savio; Praveen Thipphalli (RGUHS Journal of Medical Sciences)
Primary peritonitis typically presents with signs of peritonitis. A six-year-old female presented with fever loose stools and non-bilious vomiting for three days without abdominal pain distension guarding or rigidity. Despite the initial absence of classic peritonitis features she was found to have pyoperitoneum after three days in the hospital prompting emergency abdominal exploration. She was diagnosed with primary peritonitis and treated with peritoneal lavage and antibiotics. This case highlights how primary peritonitis can present atypically potentially misleading clinicians and leading to significant morbidity in pediatric patients.